If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4 + 20d) = -4(13 + 5d) (4 * 2 + 20d * 2) = -4(13 + 5d) (8 + 40d) = -4(13 + 5d) 8 + 40d = (13 * -4 + 5d * -4) 8 + 40d = (-52 + -20d) Solving 8 + 40d = -52 + -20d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '20d' to each side of the equation. 8 + 40d + 20d = -52 + -20d + 20d Combine like terms: 40d + 20d = 60d 8 + 60d = -52 + -20d + 20d Combine like terms: -20d + 20d = 0 8 + 60d = -52 + 0 8 + 60d = -52 Add '-8' to each side of the equation. 8 + -8 + 60d = -52 + -8 Combine like terms: 8 + -8 = 0 0 + 60d = -52 + -8 60d = -52 + -8 Combine like terms: -52 + -8 = -60 60d = -60 Divide each side by '60'. d = -1 Simplifying d = -1
| ab^2-2ab-35a= | | 20-20u+16=-18u-2(10u+18) | | 7(m-2)+4(m+6)= | | 5(x-1)-2(x-7)=4(x+2) | | -4x-3=45 | | y^4+2y^2+1= | | 6(3c+5)-16c=8c | | 5(x+1)-1(x-7)=4(x+2) | | x/3+10=-3 | | -16+7s=2(-3s+13)+10s | | 4(-2c)= | | 5(x+6)=10x-7 | | 100+20=460 | | -3(-3f)= | | 4(-f+19)=-17f-15 | | (h+3)+2= | | -3(-20b+6)-17=5(8b+13) | | (v+2)+1= | | 3r=6{-9} | | (1+4v)(2)= | | -15+x=-6 | | -13.6n-13.87=-11.5n+11.54 | | 2(4u)= | | 4(2x-1)=2(x+7) | | 4(2n+3)+5(n-3)= | | (2c)(7)= | | 11.59-10.2z=-12.7z-15.25+0.3z | | 2(4n)= | | 6(4h+1)= | | 3(2j)= | | 5(x+1)=1(x+3) | | -13.3m+12.54=10.92-13.4m |